E MUSCULOSKELETAL DISORDERS (MS PENGARUH WORKPLACE STRETCHING EXERCISE TERHADAP PENURUNAN KELUHAN MUSCULOSKELETAL DISORDERS(MSDs) PADA PEKERJA BATIK TULIS DI KECAMATAN SOKARAJA - siti harwanti; Nur Ulfah; Budi Aji (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
Batik maked process especially “mbironi”, is done in sit position. If this position maintained for a long period, that could be cause muscle strain which may lead into musculoskeletal disorders. The research was aim to know the effect of Workplace Stretching Exercise (WSE) to reduced MSDs in hand-made batik workers. The research was quasy experimental by non-equivalent control group design. Subjects were 37 female handmade batik workers used purposive sampling. Data analysis used Friedman test and Wilcoxon test, then for two independent sample used Independent t Test and Mann Whitney test with significancy level at 5% or α = 0,05. Analysis result show that there is no difference in MSDs on experiment and control group after pre-test which had p-value = 0,371 (>0,05). The result of middle-test and post-test p value = 0,000 (<0,05) that there is significant mean difference of MSDs between experiment and control group. Based on the middle-test and post-test analysis result, it could be conclude that there is an effect of WSE to reduce MSDs of handmade batik workers.